PEMBELAJARAN BIOLOGI BERBASIS LINGKUNGAN DALAM UPAYA PENINGKATAN LITERASI SAINS DAN PELESTARIAN KEARIFAN LOKAL MASYARAKAT BALI - I Made Subrata (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2023)
Abstract. Environment-based learning is learning that emphasizes the environment as a medium or learning resource, can contextualize biological material with the surrounding environment, because biological material is available in abundance in nature, both microscopic and macroscopic material objects. The environment acts as an open laboratory. Scientific literacy is the ability to use scientific knowledge, identify questions, and draw conclusions based on existing evidence in order to understand and make decisions regarding nature and changes made to nature through human activities. Environmentally based Biology learning will be able to improve students' literacy skills through observation, data collection, data analysis and communicating the results of data analysis. Local wisdom (local knowledge, local wisdom) acts as a source of innovation and skills that can be empowered for the welfare of society. Local wisdom related to natural wealth, culture and customs contains a moral message that society always protects natural wealth and traditional traditions so that they do not change with developments over time. The science of biology, which discusses living things, including their varieties, origins, habitat, interactions, utilization and sustainability, has been philosophically reflected in the community's way of life in the form of local wisdom. The purpose of writing this article is to reveal that through environment-based biology learning as a learning resource that is linked to the local wisdom of the community, students will be able to improve the scientific literacy skills and preserve the local wisdom of the local community. This writing method uses a literature review method combined with direct experience in the community. The preservation of the local wisdom of the Balinese people has been carried out through the application of the Tri Hita Karana teachings, which are three causes of prosperity that originate from harmonious relationships which include the relationship between humans and God, humans and the surrounding environment, and humans and each other. The implementation of the Tri Hita Karana teachings is carried out through concrete actions and through the implementation of religious rituals that contain environmental conservation values.